Relationship of Anti-Desmoglein-3 Antibody Titres by ELISA with ClinicalABSIS Scoring in Pemphigus Vulgaris - Anisha Manocha; Madhukara J; Rajalakshmi Tirumalae (RGUHS Journal of Medical Sciences)
Background Pemphigus vulgaris PV is a severe potentially life-threatening autoimmune blistering disease that is relatively common in India and occurs due to circulating autoantibodies against Desmoglein Dsg3. Diagnosis is based on clinical features histopathology and immunofluorescence findings IF. ELISA against Dsg 3 has been developed which is highly sensitive and specific. There is a scarcity of Indian data about the utility of ELISA in patients with PV.Aim To detect antibodies to Dsg-3 for diagnosing Pemphigus vulgaris using ELISA and correlate levels of Desmoglein-3 with ABSIS clinical severity score.Methods Two serum samples were collected from 27 confirmed patients of PV. The diagnosis was confirmed on histopathology andor IF. The first sample was taken at diagnosis and the second at least 6 weeks after instituting therapy. These samples were tested for antibodies against Dsg-3 using semi-quantitative ELISA. Correlation of ELISA results with clinical severity scoring ABSIS was done.Results We found a positive association between the total and cutaneous ABSIS scores with ELISA titres in both samples. The oral mucosal score however showed a positive association in the first set of samples and a negative association in the second set of samples. However none of these were found to be statistically significant.Conclusion Although ELISA for Dsg-3 is a very sensitive tool for the initial diagnosis of PV its utility inassessing disease activity is limited and the results should be interpreted cautiously.